Beam shaping to enhance zero group velocity Lamb mode generation in a composite plate and nondestructive testing application. (January 2017) - Faëse, Frédéric; Raetz, Samuel; Chigarev, Nikolay; Mechri, Charfeddine; Blondeau, James; Campagne, Benjamin; Gusev, Vitalyi E.; Tournat, Vincent
Abstract: Zero group velocity (ZGV) Lamb modes have already shown their potential in nondestructive testing applications as they are sensitive to the sample structural characteristics. In this paper, we first consider an aluminum sample to validate a method based on the beam shaping of the generation laser. This method is proven to enhance ZGV Lamb modes in aluminum, and then advantageously applied to a composite material plate. Finally, based on the proposed method, scanning the sample over healthy and flawed zones demonstrates the ability to detect subsurface flaws. Abstract : Highlights: ZGV Lamb mode enhancement thanks to the use of a laser beam shaping mask. Subsurface flaw detection in composite material using ZGV Lamb mode. Defect detection by a non contact laser ultrasonic method in a composite plate. Proof of principle in using ZGV Lamb mode to characterize subsurface flaw.